Subjective Memory Ability and Long-Term Forgetting in Patients Referred for Neuropsychological Assessment - van der Werf, Sieberen P.; Geurts, Sofie; de Werd, Maartje M. E. (Frontiers in Psychology, 2016)
It has been suggested that the memory complaints of patients who are not impaired on formal memory tests may reflect accelerated forgetting. We examined this hypothesis by comparing the one-week delayed recall and recognition test performance of outpatients who were referred for neuropsychological assessment and who had normal memory performance during standard memory assessment with that of a non-patient control group. Both groups performed equally in verbal learning and delayed recall. However, after one week, the patients performed worse than controls on both recall and recognition tests. Although subjective memory ability predicted short-term memory function in patients, it did not predict long-term delayed forgetting rates in either the patients or controls. Thus, long-term delayed recall and recognition intervals provided no additional value to explain poor subjective memory ability in the absence of objective memory deficits.